Character Education for Developing State Police School Students’ Bhayangkara Character Philosophy in the Society 5.0 Era - Taufik, Regul; Nurhayati, Sri (Universitas Pendidikan Mandalika, 2023)
This study aims to describe the implementation of character education management as a solution for developing State Police School Students’ Bhayangkara character philosophy in the society 5.0 era at West Java State Police School. This research applied a qualitative approach with a descriptive method. The subjects of this research involved 24 West Java State Police School Students, 1 instructor, and 1 Commander. The data collection technique was observation, document analyses, and in-depth interviews. The data analysis technique referred to interactive model data analysis, while the data validity technique is triangulation. The findings showed that: 1) character education and development process for West Java State Police School students was conducted through a series of sequential activities. These stages include material delivery, simulation, practice, formation of small groups, monitoring, and evaluation. 2) the character education program at West Java State Police School has several positive outcomes: a) Increased discipline and accountability. b) Improved communication and teamwork abilities. c)Enhanced decision-making capacity. d) Development of a Bhayangkara personality. The character education program helps students internalize the values and traits of the National Police. They are expected to exhibit commendable attitudes, such as honesty, discipline, responsibility, cooperation, and good ethics.